DESIGN AND CONSTRUCTION OF ROBUSTA COFFEE BEAN ROASTING EQUIPMENT (Coffea canephora): RANCANG BANGUN ALAT PENYANGRAI BIJI KOPI ROBUSTA(Coffea canephora) - yusran, yusran akbar; Abdullah, Umar Husein; Aulia, Rian; Agustina, Sri (PT. ROCE WISDOM ACEH, 2024)
This study aims to design a roaster to produce three roasting categories: light roast, medium roast, and dark roast and obtain quality coffee beans. The research was conducted in the laboratory of the Agricultural Mechanization Workshop of the Politeknik Indonesia Venezuela. This research uses the Trial and Error method. This research uses the Trial and Error method. During the process of roasting coffee beans, observations were made of temperature, length of time and knowing the maximum capacity of the tube and the maximum temperature level of roasting. The design of the coffee bean roaster is also classified as different from other tools or machines because it uses a heating element (heater) that can be adjusted according to the roasting desire. The response method in this study includes the temperature and length of time used during the roasting process where a system to control the situation so that the results obtained correspond to the desired value as effectively as possible. Based on the results of functional and structural tests, the roaster that has been designed can work properly. The capacity of the roasting tube that has been designed produces a volume of 9.42 liters equivalent to a coffee weight of 2 kg. The working capacity of the tool produces 2.4 kg/hour for Light Roast criteria, for Medium Roast criteria produces 1.7 kg/hour, and for Dark Roast criteria produces 0.8 kg/hour. The average temperature distribution for Light Roast material is 97 ° C, Medium Roast is 110.83° C, and Dark Roast is 131.25° C.